Morfologi Zeylanicobdella arugamensis di ikan kerapu macan (Epinephelus fuscoguttatus) menggunakan metode scanning elektron mikroskop di Pulau Lampung, Indonesia - Wolgas Angga Diputra; S.S. Bendryman (Airlangga University, 2022)
This research aims to study the morphology of Zeylanicobdella arugamensis infesting tiger grouper (Epinephelus fuscoguttatus) at Lampung Bay Waters by using scanning electron microscope (SEM). The samples of (Epinephelus fuscoguttatus) were obtained from body surface of tiger grouper (Epinephelus fuscoguttatus). Zeylanicobdella arugamensis infesting tiger grouper has an elongated body silindris with sucker in anterior and posterior. Based on the results of SEM , This parasite has a length of 4 - 4.1 mm and a width of 0.5 mm with anterior suckers and a gap in the middle surrounded by cuticle projections shaped like flower petals and white cilia with a diameter of 0.3 - 0.4 mm and posterior suckers part with a diameter of 0.9 - 1.4 mm where the size is larger than the anterior sucker. On the ventral surface of the body there is a transverse segmented coelom which is separated from the body cavity. Keywords: Tiger grouper, Zeylanicobdella arugamensis, Scanning Electrone Microscope (SEM), Hirudinea